Βιβλιοκρισία: Documents Concerning Cyprus from the Hospital’s Rhodian Archives: 1409-1459, εκδ. K. BORCHARDT, A. LUTTRELL, E. SCHÖFFLER [Cyprus Research Centre. Texts and Studies in the History of Cyprus –LXVI], Λευκωσία 2011, xcii + 550 σελ. - ΚΟΥΜΑΝΟΥΔΗ Μαρίνα (Byzantina Symmeikta, 2015)
Βιβλιοκρισία: Documents Concerning Cyprus from the Hospital’s Rhodian Archives: 1409-1459, εκδ. K. Borchardt, A. Luttrell, E. Schöffler [Cyprus Research Centre. Texts and Studies in the History of Cyprus –LXVI], Λευκωσία 2011, xcii + 550 σελ., ISBN 978-9963-0-8124-0.